Criticism Toward American Democracy And Capitalism Reflected In Suzanne Collins's The Hunger Games Trilogy (2008-2010) - Afiani, Isyfi, Dr. M. Thoyibi, M.S (2015)
This study delves out the criticism toward American democracy and capitalism reflected in Suzanne Collins's The Hunger Games trilogy-The Hunger Games (2008), Catching Fire (2009), and Mockingjay (2010)-by using Marx's theory of class struggle. This study belongs to the literary study. The technique of data collection is document analysis; meanwhile the technique of data analysis is descriptive technique. This study uses two data sources; they are primary and secondary data source. The primary data source of the study is Suzanne Collins's The Hunger Games trilogy that consists of three novels; The Hunger Games (2008), Catching Fire (2009), and Mockingjay (2010). Meanwhile, the secondary data source of this study are taken from other sources such as literary books, previous studies, articles, journals, and also website related to the trilogy of The Hunger Games trilogy. This study is aimed to investigate the problem of American democracy and capitalism reflected in The Hunger Games trilogy through the class struggle analysis-the class differences, the cause of class struggle, power relation, the effect of class struggle, the type of class struggle. The class struggle analysis is brought in to contrast and compare the dystopian society of Panem with America in the 21st century. This study shows that the class struggle reflected in trilogy is seen as the vehicle to criticize the American democracy and capitalism.